Increasing Elementary School Students' Understanding of Natural Disaster Mitigation through Visual Education Media - Riana, Daffa Affanin; Mustoip, Sofyan; Ara, Kamilah Danish (EduBase : Journal of Basic Education, 2024)
This research aims to increase elementary school students' understanding of natural disaster mitigation through the use of visual educational media. A qualitative approach was used in this research, with a research design in the form of a case study in one of the elementary schools in a disaster-prone area. Data was collected through observation, in-depth interviews, and document analysis. The visual educational media developed includes illustrations, animated videos, and infographics that explain types of natural disasters, mitigation steps, and self-saving measures. The research results show that the use of visual educational media significantly increases students' understanding of the concept of disaster mitigation, as seen from the increase in student participation in learning and their ability to explain mitigation steps independently. This research provides recommendations for developing more innovative and technology-based learning media to support disaster education in elementary schools.